Agonistic approaches to sexuality: A critical analysis of the conservative mindset - Timo Airaksinen (Heliyon, 2023)
Why do so many people attack sexualities they do not desire and which do not harm them independently of their negative emotions? This is a question to conservative audiences whose anxious reactions this study aims to explain. I introduce seven principles to clarify the situation. The Foundational Principle sketches the basic normative rules. The Hyperbolic Principle recognizes the ever-present exaggeration of sex narratives. According to the Imaginary Principle, extreme imaginings will become too painful to bear. The Principle of de se Reading of Sexual Thought explains contagious emotions and vicarious arousal. The Principle of Motivation argues that sexual images are intrinsically arousing and thus prima facie motivating. According to the Principle of Safety, an unacceptable sexual desire feels unsafe and risky. The Exclusionary Principle says, if a person fails to recognize a given sexual desire, she rejects it. This is the principle that characterizes a conservative reaction to unaccepted sexuality. These negative socio-psychological facts have not attracted adequate attention in sexuality studies. Yet, anxious conservative audiences have the political power to jeopardize liberal policy formation, sex education, and LGBT/BDSM lifestyles. The method of this study is conceptual and philosophical. Its premises and result should lead to empirical verification. At the same time, I suggest a more sophisticated conceptual and linguistic framework for advancing the critical discussion of moral tradition, scientific sexuality studies, and diagnostic art.